Tranexamic acid reduces perioperative blood transfusions following open radical cystectomy: a propensity-score matched analysis - Egen, Luisa; Keller, Karoline; Menold, Hanna; Quan, Allison; Dempfle, Carl-Erik; Schöttler, Jochen; Wessels, Frederik; Meister, Benjamin; Worst, Thomas; Westhoff, Niklas Christian; Kriegmair, Maximilian; Honeck, Patrick; et al. (World journal of urology, 2024)
Purpose Radical cystectomy is associated with bleeding and high transfusion rates, presenting challenges in patient management. This study investigated the prophylactic use of tranexamic acid during radical cystectomy. Methods All consecutive patients treated with radical cystectomy at a tertiary care university center were included from a prospectively maintained database. After an institutional change in the cystectomy protocol patients received 1 g of intravenous bolus of tranexamic acid as prophylaxis. To prevent bias, propensity score matching was applied, accounting for differences in preoperative hemoglobin, neoadjuvant chemotherapy, tumor stage, and surgeon experience. Key outcomes included transfusion rates, complications, and occurrence of venous thromboembolism. Results In total, 420 patients were included in the analysis, of whom 35 received tranexamic acid. After propensity score matching, 32 patients and 32 controls were matched with regard to clinicopathologic characteristics. Tranexamic acid significantly reduced the number of patients who received transfusions compared to controls (19% [95%-Confidence interval = 8.3; 37.1] vs. 47% [29.8; 64.8]; p = 0.033). Intraoperative and postoperative transfusion rates were lower with tranexamic acid, though not statistically significant (6% [1.5; 23.2] vs. 19% [8.3; 37.1], and 16% [6.3; 33.7] vs. 38% [21.9; 56.1]; p = 0.257 and p = 0.089, respectively). The occurrence of venous thromboembolism did not differ significantly between the groups (9% [2.9; 26.7] vs. 3% [0.4; 20.9]; p = 0.606). Conclusion Prophylactic tranexamic administration, using a simplified preoperative dosing regimen of 1 g as a bolus, significantly lowered the rate of blood transfusion after cystectomy. This exploratory study indicates the potential of tranexamic acid in enhancing outcomes of open radical cystectomy.